1989
DOI: 10.1029/ja094ia01p00435
|View full text |Cite
|
Sign up to set email alerts
|

Application of bicoherence analysis in study of wave interactions in space plasma

Abstract: A spectral analysis at the second order (power spectrum) loses the phase information among the different Fourier components. To retain this information, the bispectrum (third order) and/or the bicoherence (normalized bispectrum) are calculated. Application to simulated data, shows the dependence of the bispectrum to amplitudes of involved waves and of the bicoherence to signal‐to‐noise ratio. Bicoherence technique is applied in the analysis of harmonics produced by an electronic receiver, as well as in the inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 12 publications
(10 reference statements)
3
18
0
Order By: Relevance
“…The Fourier bispectrum can be misleading for short data records, for which large values of B ( ω 1 , ω 2 ) can be generated even though the signal is incoherent, i.e., with no phase relations. This is due to the sensitivity of the bispectrum to the amplitudes of the spectral components involved [ Lagoutte et al , ]. Thus, in this study, we opt for a normalized quantity called the bicoherence, which is defined as b2(ω1,ω2)=|B(ω1,ω2)|2E[]|F(ω1)F(ω2)|2E[]|F(ω1+ω2)|2 and its values lie between 0 and 1.…”
Section: Higher‐order Power Spectramentioning
confidence: 99%
“…The Fourier bispectrum can be misleading for short data records, for which large values of B ( ω 1 , ω 2 ) can be generated even though the signal is incoherent, i.e., with no phase relations. This is due to the sensitivity of the bispectrum to the amplitudes of the spectral components involved [ Lagoutte et al , ]. Thus, in this study, we opt for a normalized quantity called the bicoherence, which is defined as b2(ω1,ω2)=|B(ω1,ω2)|2E[]|F(ω1)F(ω2)|2E[]|F(ω1+ω2)|2 and its values lie between 0 and 1.…”
Section: Higher‐order Power Spectramentioning
confidence: 99%
“…The bicoherence is used as an estimator of quadratic phase coupling, characteristic of three‐wave coherent interactions. Lagoutte et al [1989] give a methodological introduction to bicoherence analyses based on a Fourier approach. Although studies of bicoherence have been reported in the ionosphere [ Pecseli et al , 1993], the bow shock [ Dudok de Wit and Krasnosel'Skikh , 1995] and the solar wind near the foreshock edge [ Bale et al , 1996], to our knowledge, the present analyses represents the first time that bicoherence is used to study three‐wave coupling in the solar wind during a type III.…”
Section: Evidence For Wave Couplingmentioning
confidence: 99%
“…Historically 3 approaches to the identification of nonlinear processes have been used: bicoherency (Kim and Powers, 1979;Lagoutte and Hanasz, 1989), time domain modelling (Coca et al, 2001;Zhu et al, 2007) and frequency domain modelling (Ritz and Powers, 1986). The main advantage of bicoherency is that it can be applied to single point measurements.…”
Section: Introductionmentioning
confidence: 99%